Effect of gut microbiota changes on cytokines IL-10 and IL-17 levels in liver transplantation patients - Mohamed Abdel-Raoof Fouda; Mohamed Abdel-Wahhab; Ahmed Esmail Abdelkader; Mohsen El-Sayd Ibrahim; Taher Abozeid Elsheikh; Hisham Mohammad Aldeweik; Nora Elfeky (BMC Infectious Diseases)
Abstract Background Liver transplantation (LT) is a critical intervention for individuals with end-stage liver disease; yet, post-transplant problems, especially infections, graft rejection, and chronic liver disease, are often linked to systemic inflammation. Cytokines, small signaling molecules, significantly influence immune responses during and post-liver transplantation. Nonetheless, the intricate relationships among cytokines, immune responses, and the gut microbiota, especially gut dysbiosis, are still inadequately comprehended. Thus, this study aims to identify the gut microbiota (GM) and determine their relationship to cytokines (IL-17 and IL-10) in LT patients, due to their importance in enhancing the recovery rate. Result The research included 31 liver transplant (LT) patients from the Gastroenterology Surgical Center at Mansoura University, resulting in the collection of 174 stool and blood samples from all participants. Fourteen bacterial species have been identified in samples collected at three intervals: one week before, one week post, and two weeks post LT. A change in gut microbiota composition was noted, characterized by a rise in potentially pathogenic bacteria such as Enterococci and Enterobacteriaceae (including Escherichia coli and Klebsiella) and a reduction in beneficial bacteria such as Bacteroidetes and Firmicutes. The examination of patient demographic and clinical data revealed no significant correlations between sex, age, or diagnostic categories and gut microbiota composition. The findings of the Multivariate Analysis of Variance (MANOVA) indicated a substantial effect of gut microbiota composition on cytokine levels (IL-10 and IL-17), with all tests producing p-values of 0.001. The assessment of cytokine levels indicated fluctuating variations at several time points following surgery. IL-10 levels in the GM groups exhibited a statistically significant elevation during the second week post-surgery (p = 0.036), suggesting a potential recovery-related anti-inflammatory response. In contrast, IL-17 levels rose in the NI group over time, indicating a transition to a pro-inflammatory condition. Conclusion This study emphasizes the pivotal role of the gut microbiota in regulating immune responses following transplantation.